Trade-Offs Associated with Photoprotective Green Fluorescent Protein Expression as Potential Drivers of Balancing Selection for Color Polymorphism in Reef Corals - Quick, Cathryn; D'Angelo, Cecilia; Wiedenmann, Jörg (Frontiers in Marine Science, 2018)
Photodamage of symbiotic algae exposed to thermal stress is involved in mass coral bleaching, a major cause of reef decline. Photoprotection is therefore a vital part of coral stress physiology. Corals produce a variety of green fluorescent protein (GFP)-like proteins from which some representatives screen the symbiotic algae from excess light. Different tissue concentrations of these GFP-like proteins distinguish colour morphs that are characteristic for many coral species. The question arises whether these pigmentation differences may diversify the niches that can be occupied by corals along the steep light gradient that structures coral reef communities. We assessed the implications of GFP-like protein expression in two color morphs of the symbiotic coral Hydnophora grandis, both associated with the same Symbiodinium sp. (subclade C40). The colour morphs of this species (high fluorescent, HF; and low fluorescent, LF), characterized by markedly different contents of a cyan fluorescent protein, were exposed to different quantities of blue light (470nm) that matched the major absorption band of the host pigment (473nm). High intensities of blue light caused less photodamage to the symbiotic algae of the HF morph and resulted in higher growth rates of these corals compared to representatives of the LF morph. In contrast, under low intensities of blue light, the HF morph showed lower growth rates than the LF morph, indicating that trade-offs are associated with high levels of fluorescent protein expression under this condition. Both morphs showed highest growth rates at medium light intensities with no obvious influence of the tissue pigmentation. Reef coral colour polymorphism caused by photoprotective GFP-like proteins may therefore be a product of balancing selection in which high pigment contents may be beneficial at the upper and detrimental at the lower end of the depth distribution range of symbiotic corals. Conversely, colour morphs with GFP-like proteins that function to optimize symbiont photosynthesis in low light environments could gain an advantage from the benefits offered by high pigment levels in deeper waters.